Enzyme/GSH/pH-responsive hyaluronic acid grafted porous silica nanocarriers bearing Ag2S QDs for fluorescence imaging and combined therapy. (1st April 2023) - Hou, Jun; Zhao, Yanbao; Sun, Lei; Zou, Xueyan
Abstract: Hyaluronic acid (HA) is a naturally polysaccharide that has been used for drug delivery, but is limited by low drug loading capacity and drug leakage in circulation. To improve drug delivery efficient, HA modified porous silica (pSiO2 ) nanocarriers were successfully prepared for drug delivery and combining therapy. pSiO2 nanocarriers have stable porous structure and high loading capacity, and pSiO2 /HA nanocarriers would possess advantages of HA-based carriers and pSiO2 nanoparticles. Herein, pSiO2 nanocarriers were prepared by two-phase process, followed by embedding Ag2 S QDs in the pore walls of pSiO2 carriers, which render the carriers photothermal effect. pSiO2 nanocarriers have size of 30 nm, large channels, and high loading capacity (29.3 %). To graft HA, a sensitive linker with alkyl amine and disulfide bond was conjugated on the surface of Ag2 S/pSiO2 nanocarriers by three-step reaction. After loading doxorubicin (DOX), HA was grafted via sensitive linker onto the surface of Ag2 S/pSiO2 carriers via the formation of amide bonds to seal the loaded drugs. The interaction between HA and CD44 confers the carrier targeting ability to cancer cells. HA coating can be degraded by hyaluronidase resulting in the release of internal cargo. The Ag2 S/pSiO2 /HA nanocarriers performs responsive drug release and combining photothermal chemotherapy. Graphical abstract: Unlabelled Image